Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To find the inverse of the function [tex]\( y = 2x^2 + 2 \)[/tex], we need to follow these steps.
### Step-by-Step Solution:
1. Write the function:
[tex]\[ y = 2x^2 + 2 \][/tex]
2. To find the inverse, swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex]:
[tex]\[ x = 2y^2 + 2 \][/tex]
3. Solve for [tex]\( y \)[/tex]:
First, subtract 2 from both sides:
[tex]\[ x - 2 = 2y^2 \][/tex]
Then divide both sides by 2:
[tex]\[ \frac{x - 2}{2} = y^2 \][/tex]
4. Take the square root of both sides:
[tex]\[ y = \pm \sqrt{\frac{x - 2}{2}} \][/tex]
5. Simplify the expression:
The two solutions are:
[tex]\[ y = \sqrt{\frac{x - 2}{2}} \quad \text{and} \quad y = -\sqrt{\frac{x - 2}{2}} \][/tex]
Hence, the inverse functions are:
[tex]\[ y = \sqrt{\frac{x - 2}{2}} \quad \text{and} \quad y = -\sqrt{\frac{x - 2}{2}} \][/tex]
These solutions correspond to:
[tex]\[ \pm \sqrt{\frac{x - 2}{2}} \][/tex]
Thus, the correct choice from the given options is:
[tex]\[ y = \pm \sqrt{\frac{x - 2}{2}} \][/tex]
However, it appears that there is a slight error in the provided options. Correcting the inverse function form, we get:
[tex]\[ y = \pm \sqrt{\frac{x - 2}{2}} \][/tex]
So the actual correct form which wasn't perfectly matched in the given options is:
[tex]\[ \pm \sqrt{\frac{x - 2}{2}} \][/tex]
### Step-by-Step Solution:
1. Write the function:
[tex]\[ y = 2x^2 + 2 \][/tex]
2. To find the inverse, swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex]:
[tex]\[ x = 2y^2 + 2 \][/tex]
3. Solve for [tex]\( y \)[/tex]:
First, subtract 2 from both sides:
[tex]\[ x - 2 = 2y^2 \][/tex]
Then divide both sides by 2:
[tex]\[ \frac{x - 2}{2} = y^2 \][/tex]
4. Take the square root of both sides:
[tex]\[ y = \pm \sqrt{\frac{x - 2}{2}} \][/tex]
5. Simplify the expression:
The two solutions are:
[tex]\[ y = \sqrt{\frac{x - 2}{2}} \quad \text{and} \quad y = -\sqrt{\frac{x - 2}{2}} \][/tex]
Hence, the inverse functions are:
[tex]\[ y = \sqrt{\frac{x - 2}{2}} \quad \text{and} \quad y = -\sqrt{\frac{x - 2}{2}} \][/tex]
These solutions correspond to:
[tex]\[ \pm \sqrt{\frac{x - 2}{2}} \][/tex]
Thus, the correct choice from the given options is:
[tex]\[ y = \pm \sqrt{\frac{x - 2}{2}} \][/tex]
However, it appears that there is a slight error in the provided options. Correcting the inverse function form, we get:
[tex]\[ y = \pm \sqrt{\frac{x - 2}{2}} \][/tex]
So the actual correct form which wasn't perfectly matched in the given options is:
[tex]\[ \pm \sqrt{\frac{x - 2}{2}} \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.